Assessment of information systems for enterprise development - A.O. Kolomyceva; T.O. Zagorna (Marketing i Menedžment Innovacij, 2011)
In article are analyzed reasons to inefficiency of the introducing the corporative information systems on Ukrainian enterprise, as well as prospects of the using the corporative information systems on base parallel-round-robin model of the company. On this base is designed procedure of the estimation and regulations level to efficiency of the computer information systems.